Growth and Productivity in Papua New Guinea - Faal, Ebrima (IMF Working Papers; Working Paper, 2006)
This paper has examined Papua New Guinea's historical economic growth patterns through a simple growth accounting framework. The analysis shows that swings in growth are mostly accounted for by a significant slowdown in capital input and lower Total Factor Productivity (TFP) growth. It also suggests that raising real GDP growth will require increases in both investment levels and productivity. With a ratio of investment to GDP of 13 percent during the last decade, significantly higher productivity growth and investment will be needed to sustain GDP growth rates at 5 percent or higher. The historical performance also indicates that, in the absence of structural reforms and strong institutions, higher rates of productivity growth will be hard to achieve.